New paradigms in clonal evolution: punctuated equilibrium in cancer - Cross, William CH; Graham, Trevor A; Wright, Nicholas A (The Journal of pathology, 2016)
Evolutionary theories are themselves subject to evolution. Clonal evolution – the model that describes the initiation and progression of cancer – is entering a period of profound change, brought about largely by technological developments in genome analysis. A flurry of recent publications, using modern mathematical and bioinformatics techniques, have revealed both punctuated and neutral evolution phenomena that are poorly explained by the conventional graduated perspectives. In this review, we propose that a hybrid model, inspired by the evolutionary model of punctuated equilibrium, could better explain these recent observations. We also discuss the conceptual changes and clinical implications of variable evolutionary tempos. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.